Two-color 810 nm STED nanoscopy of living cells with endogenous SNAP-tagged fusion proteins - Butkevich, Alexey N.; Hell, Stefan (ACS chemical biology, 2017)
A 810 nm STED nanoscopy setup and an appropriate combination of two fluorescent dyes (Si-rhodamine 680SiR and carbopyronine 610CP) have been developed for near-IR live-cell super-resolution imaging. Vimentin endogenously tagged using the CRISPR/Cas9 approach with the SNAP tag, together with a noncovalent tubulin label, provided reliable and cell-to-cell reproducible dual-color confocal and STED imaging of the cytoskeleton in living cells.